THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON INNOVATIVE WORK BEHAVIOR OF EMPLOYEES OF THE COMMUNICATION AND INFORMATICS SERVICE OF BINJAI CITY - Aditya Mulia Sembiring; Yeni Absah; Nismah Penjaitan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this study is work motivation in mediating the influence of organizational culture on the innovative work behavior of employees of the Binjai City Communication and Informatics Office. The approach in this study uses an associative approach. The study was conducted at the Binjai City Communication and Informatics Office. The determination of this area was done purposively. The study was conducted from January 2025 to March 2025. The sample in this study was all employees of the Binjai City Communication and Informatics Office, namely 20 people. In this study, hypothesis testing was carried out using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS) or abbreviated as SEM - PLS. The results of the study The relationship between organizational culture and work motivation is positive and significant. The relationship between organizational culture and innovative work behavior is positive and significant. The relationship between work motivation and innovative work behavior is positive but not significant. The mediation relationship between work motivation and organizational culture and innovative work behavior is not significant.